Recent Publications (Quarterly Journal of Economics, 1956)
Recent Publications Get access The Quarterly Journal of Economics, Volume 70, Issue 3, August 1956, Pages 478–480, https://doi.org/10.1093/qje/70.3.478 Published: 01 August 1956